EFEK FERMENTASI LIMBAH SAYUR DENGAN DOSIS MOL YANG BERBEDA TERHADAP KANDUNGAN (NDF,ADF,HEMISELULOSA): EFEK FERMENTASI LIMBAH SAYUR DENGAN DOSIS MOL YANG BERBEDA TERHADAP KANDUNGAN (NDF,ADF,HEMISELULOSA) - Nonni Anggriani; Neli Definiati; Edwar Suharnas; Wismalinda Rita; Lezita Malianti (Jurnal Inspirasi Peternakan, 2022)
NONNI ANGGRIANI, EFFECTS OF VEGETABLE WASTE FERMENTATION WITH DIFFERENT DOSAGE OF MOLE ON CONTENT (NDF,ADF,HEMISLULOSE) Under the guidance of I. Neli Definiati SP, MP., Supervisor II. Ir. Edward Suharnas MP. Animal Husbandry Study Program, Faculty of Agriculture and Animal Husbandry, University of Muhammadiyah Bengkulu 2022. The purpose of this study was to determine the effect of adding moles to fermented vegetable waste on the cellulose and lignin content by proximate analysis. This research was carried out in August until completion, the manufacture of MOL of vegetable waste was carried out at the Laboratory of the Faculty of Agriculture and Animal Husbandry, University of Muhammadiyah Bengkulu and Proximate Analysis of Neutral Content of Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and Hemicellulose was carried out at the Dairy Animal Nutrition Laboratory of the Institute Bogor Agriculture (IPB). This study used a completely randomized design with 4 treatments and 4 replications. Treatment A was fermented vegetable waste with the addition of 3% MOL, B vegetable waste was fermented with the addition of 6% MOL, C vegetable waste was fermented with the addition of 9% MOL and D vegetable waste was fermented with the addition of 12% MOL. The parameters observed were the fiber content of vegetable waste including Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and Hemicellulose. The results showed that giving different mole doses significantly affected the content of Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and Hemicellulose. With the addition of different doses of MOL in vegetable waste feed, it has the effect of decreasing the content of Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and Hemicellulose. From this study it can be concluded that giving different doses of MOL to fermented vegetable waste feed can simplify the fiber fraction bond in Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and Hemicellulose so that the content of fermented feed in vegetable waste can be utilized. Keywords: Vegetable Waste, MOL dose, Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF) and Hemicellulose